Spinoza’s Conatus Undoes Bourdieu’s Habitus - Bech, Josep Maria (Conatus - Journal of Philosophy, 2021)
Bourdieu’s intermittent allusions to Spinoza’s conatus disclose the weaknesses of his concept of habitus. A thorough inspection of his involvement with the Spinozist legacy reveals a long-lasting inconsistency, for he expects that conatus will assist him in both 1) grounding the habitus and solving the uncertainties that surround this notion by endorsing a strong conatus, impervious to the resistances it will eventually encounter; and 2) re-instating agency in the structuralist mindset, a program retrospectively admitted by Bourdieu in 1987 and bound to a weak conatus, exposed to the interfering resistance of exterior forces and thus determined by the interaction with contingent events. Bourdieu noticed this incongruity around 1993. At that time, he renounced to buttressing the habitus by means of the dynamizing character of conatus. So began the later evolution of his thought, linked to the antithetical demand of both a weak and a strong conatus, a request commanded in its turn by an overarching habitus. One outcome of this conflict is that agency can hardly be summoned if Bourdieu’s conception of a “strong” conatus prevails and the dispositions making up the habitus are irreversible. In contrast, both Bourdieu’s appeal to controlled improvisation, and the ensuing concept of strategy, demand a “weak” conatus. Overall, the notion of habitus has been dubbed “a Trojan Horse for determinism” and endorses in fact what might be called the “mythology of permanence,” that is, the historically long-held belief in an all-embracing everlastingness. Bourdieu’s use of Spinoza’s conatus, in sum, besides highlighting the immutable social reproduction entailed by the habitus, acts as a litmus test for the ambiguities and shortcomings of this notion.